The association between workload, alcohol use, and alcohol misuse among psychiatrists in China - Li, Wenzheng; Chen, Long; Hsu, Michael; Mo, Daming; Xia, Lei; Min, Kaiyuan; Jiang, Feng; Liu, Tingfang; Liu, Yuanli; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Psychiatry, 2023)
Aim: Survey alcohol use and workload among Chinese psychiatrists and explore their associations. Methods: We conducted an online questionnaire among psychiatrists working in large psychiatric institutions across the country. We collected data including demographic factors, alcohol use, and workload. Alcohol use was assessed using the Alcohol Use Disorder Identification Test-Consumption (AUDIT-C), and workload-related questions included working hours, night shifts, and caseloads. Results: In total, 3549 psychiatrists completed the survey. Nearly half (47.6%) reported alcohol use, and the percentage of alcohol use in males (74.1%) was significantly higher than in females. 8.1% exceeded the AUDIT-C cutoff scores for probable alcohol misuse (19.6%in males and 2.6%in females). AUDIT-C scores were significantly correlated with working hours per week (p=0.017) and the number of outpatient visits per week (p=0.006). Regressional analysis showed that alcohol use was significantly associated with the following factors: longer working hours (Working more than 44 hours/week, OR = 1.315), having an administrative position (OR =1.352), being male (OR =6.856), being single (OR =1.601), being divorced or widowed (OR =1.888), smoking (OR =2.219), working in the West (OR =1.511) or the Northeast (OR =2.440). Regressional analysis showed that alcohol misuse was significantly associated with the following factors: fewer night shifts (Three to four night shifts/month, OR = 1.460; No more than 2 night shifts/month, OR = 1.864), being male (OR =4.007), working in the Northeast (OR =1.683), smoking (OR =2.219), frequent insomnia (OR =1.678). Conclusions: Nearly half of the psychiatrists in China reported alcohol use and 8.1% had probable AUD. Alcohol consumption is significantly associated with several workload-related factors, such as long working hours, heavy caseload, and administrative duties. Alcohol misuse was inversely associated with the number of night shifts per month. While the direction of causality is unclear, our findings may help identify vulnerable professional groups and develop more targeted interventions to improve healthcare professionals’ well-being.